Digital Literacy in Indonesian Language Learning in Elementary Schools: Literasi Digital pada Pembelajaran Bahasa Indonesia di Sekolah Dasar - Nisfah, Nurul Lailatun; Nurroh, Ermawati Zulikhatin (Indonesian Journal of Education Methods Development, 2020)
This researh entitled Digital Literacy in Indonesian Language Learning at Elementary School. This Study aims to analyze how to use of digital litracy in learning Indonesian language at elementary school. This research uses literature study research by reviewing several jurnal articles relate to the title. The result of the research conducted show that digital literacy can be used using several digital media in which learning can be carried out, especially learning Indonesian language at elementray school. So it can be concluded that digital literacy can be done in elementary schools using digital media with the assistance of a teacher or parent.